1990
DOI: 10.1016/0010-2180(90)90126-c
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of flame blowout limits by the use of swirl

Abstract: The blowout limits of a number of swirl-stabilized, nonpremixed flames were measured, and the observed trends are successfully explained by applying certain concepts that previously have been applied only to nonswirling flames. It is shown that swirl flame blowout limits can be compared to well-known limits for nonswirling simple diffusion flames by using the proper nondimensional parameter, i.e., the inverse Damkohler number (UF/dF)/(SL 2/ctF). The fuel velocity at blowout (UF) was measured while four paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(34 citation statements)
references
References 15 publications
(19 reference statements)
2
32
0
Order By: Relevance
“…Previous work with this burner has investigated the emission from the combustion of glycerol and crude glycerol from biodiesel production and is reported in the work of Bohon et al [2,3]. This setup utilizes a high swirl burner, functionally similar to that of Chen et al [13][14][15], in which two independently controlled combustion air streams create swirling flow. A schematic illustration Table 1 Thermophysical properties of fuels from DIPPR database [12].…”
Section: Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work with this burner has investigated the emission from the combustion of glycerol and crude glycerol from biodiesel production and is reported in the work of Bohon et al [2,3]. This setup utilizes a high swirl burner, functionally similar to that of Chen et al [13][14][15], in which two independently controlled combustion air streams create swirling flow. A schematic illustration Table 1 Thermophysical properties of fuels from DIPPR database [12].…”
Section: Experimental Set-upmentioning
confidence: 99%
“…The calculation of the geometric swirl number is based on the analysis of Claypole and Syred [16]. Analysis of the swirl number in this similar geometry was conducted by Feikema [15] using laser velocimetry. Their work has shown that the swirl number was proportional to the geometric swirl number times a constant with the geometric swirl number calculated using Eq.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Swirl is introduced by two coannular sets of pilot swirl vanes, and an outer annulus of main swirl vanes. Swirl improves the flame stability for reasons that are discussed in [33].…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…The swirl number, S, of jet-LSBs can be defined by the mass flow rate of the reactants, ṁ ‫ס‬ ṁ air ‫ם‬ ṁ fuel , the swirl air, ṁ h , and the total swirl injector area, A h [12,13]. 2 …”
Section: Scaling Of the Jet-lsbmentioning
confidence: 99%